Trends in willingness to receive COVID-19 vaccines among healthcare workers in India: Findings from repeated cross-sectional national surveys - Padhi, Bijaya Kumar; Chakrapani, Venkatesan; Gupta, Madhu; Sharma, Nikita; Patro, Binod Kumar; Kar, Sitanshu Sekhar; Singh, Ritesh; Pala, Star; Sankhe, Lalit; Modi, Bhavesh; Bali, Surya; Rustagi, Neeti; et al. (Frontiers in Public Health, 2022)
Background: COVID-19 vaccination of the health care workers (HCWs) is a key priority in the fight against the SARS-CoV-2 pandemic. India launched its COVID-19 vaccination program in January 2021. We aimed to understand the trends in willingness to receive COVID-19 vaccines and its associated factors among HCWs in India. Methods: Using a repeated cross-sectional survey design, we collected information from HCWs in three critical time points: before (n=937, October 2020), during (n=1346, January 2021); and after (n=812, May 2021) the introduction of COVID-19 vaccines in India. The third survey coincided with the peak of the second wave of COVID-19 pandemic in India. Findings: Of the study participants, 43.7%, 60.2%, and 73.2% were willing to receive COVID-19 vaccines during the first, second and third rounds of surveys, respectively. In multivariable logistic regression analysis, participants who trusted the health care system were more likely to report willingness to receive a COVID-19 vaccine; medical trust emerged as a significant factor in all the three rounds of surveys (First survey - aOR: 2.24, 95% CI: 1.67-2.99; Second survey - aOR: 3.38, 95% CI: 2.64-4.33; Third survey - aOR: 2.54, 95% CI: 1.65-3.91). Having confidence in domestic vaccines (Second survey - aOR: 2.21, 95% CI: 1.61-3.02; Third survey - aOR: 2.05, 95% CI: 1.24-3.37); and high perceived risk of contracting COVID-19 (Second survey - aOR: 1.48, 95% CI: 1.13-1.93; Third survey - aOR: 2.02, 95% CI: 1.31-3.13) were found to be associated with willingness to receive vaccines. Among socio-demographic characteristics, being married (aOR: 1.71, 95% CI: 1.08-2.71) and having high socio-economic status (aOR: 3.01, 95% CI: 1.65-5.51) emerged as significant factors associated with willingness to receive COVD-19 vaccines in the third round of the surveys.